1993
DOI: 10.1007/bf02871953
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the basement in the Archaean Dharwar craton of southern India and the age of the Peninsular Gneiss

Abstract: The Archaean Peninsular Gneiss of southern India is considered by a number of workers to be the basement upon which the Dharwar supracrnstai rocks were deposited. However, the Peninsular Gneiss in its present state is a composite gneiss formed by synkinematic migmatization during successive episodes of folding (DhFI, DhFI, and DhF2) that affected the Dharwar supracrustal rocks. An even earlier phase of migniatization and deformation (DhF,) is evident from relict fabrics in small enclaves of gneissic tonalites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…The zircon ages of the WDC basement gneisses and the metasediments obtained in this study are consistent with those reported earlier for gneisses from Holenarasipur, Gorur-Hassan and Chikmagalur regions of the Dharwar craton (Beckinsale et al 1980;Taylor et al 1984;Meen et al 1992;Naha et al 1993;Peucat et al 1993). A span of crystallization ages ranging from 3.0 to 3.3 Ga for the orthogneiss protoliths are evident in the data presented here and those reported earlier suggests that episodic emplacement of the TTG suite in the WDC over a time span of few hundred million years.…”
Section: Zircon Ages: Western Dharwar Craton (Wdc)supporting
confidence: 92%
See 3 more Smart Citations
“…The zircon ages of the WDC basement gneisses and the metasediments obtained in this study are consistent with those reported earlier for gneisses from Holenarasipur, Gorur-Hassan and Chikmagalur regions of the Dharwar craton (Beckinsale et al 1980;Taylor et al 1984;Meen et al 1992;Naha et al 1993;Peucat et al 1993). A span of crystallization ages ranging from 3.0 to 3.3 Ga for the orthogneiss protoliths are evident in the data presented here and those reported earlier suggests that episodic emplacement of the TTG suite in the WDC over a time span of few hundred million years.…”
Section: Zircon Ages: Western Dharwar Craton (Wdc)supporting
confidence: 92%
“…Zircons from the three orthogneissic samples from the Nuggihalli schist belt area and the orthogneissic clast from the Kaladurga conglomerate yielded ages ranging from 3.0 to 3.26 Ga. Ages of 3.2 Ga for the core region in heterogeneous zircons in these samples are comparable to the reported 207 Pb-206 Pb zircon and Rb-Sr whole rock ages of 3.0 to 3.3 Ga for the gneisses from the Gorur-Hassan region in the WDC (Beckinsale et al 1980;Naha et al 1993;Peucat et al 1993). Concordant ages seen in both individual zircons and in multiple analyses within single zircons (table 2) and the well-preserved core-overgrowth age relationship validates the identification of the magmatic component in our dataset for these three gneissic samples and indicates that the inferred ages of 3.1 Ga is close to their formation age.…”
Section: Zircon Ages: Western Dharwar Craton (Wdc)supporting
confidence: 80%
See 2 more Smart Citations
“…3.3 to 2.5 Ga (Beckinsale et al, 1980;Beckinsale and Reeves-Smith, 1982;Jayananda et al, 2000). The PGC of Western Dharwar craton represents one of the oldest rocks in India and dates back to 3.3 to 3.4 Ga as determined by Rb-Sr and Pb-Pb methods (Bhaskar Rao et al, 1991;Naha et al, 1993). U-Pb zircon ages ranging from 3.5 to 3.6 Ga have also been published (Meert et al, 2010).…”
Section: Peninsular Gneissic Complexmentioning
confidence: 94%